KEDUDUKAN DAN PERANAN ORANG LANJUT USIA DALAM KELUARGA DAN MASYARAKAT - Murlis, Murlis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Elderly people can be categorized both socially and biologically. Socially elderly people are characterized by a person's age, because age is our interaction with other people in the social environment. With certainty, old age cannot be determined because socially elder people will be treated like parents, even though they do not feel old. In the social stratification of the elderly, there will be changes in social status and social roles. In modern society, the existence of parents in the child's family can be a problem, namely it can interfere with the economic life of the child's family, shared affection, and perhaps household problems due to the involvement of parents in the child's family affairs. The tendency of modern society today to form a nuclear family brings problems with the lives of the elderly. The role and position of the elderly in the family and society are very much influenced by cultural views about aging. Different views on the elderly will make attitudes and respect for elderly people different in society and in the family.